МОДИФІКОВАНА ДВОПОЛЮСНА ЗАСТУПНА СХЕМА, ЕКВІВАЛЕНТНА ЛІНІЙНОМУ ЕЛЕКТРИЧНОМУ КОЛУ СИНУСОЇДНОГО СТРУМУ ЗА КОМПЛЕКСНОЮ ПОТУЖНІСТЮ, ДЛЯ ОПТИМІЗАЦІЇ ТА ВИМІРЮВАННЯ ЙОГО ЕНЕРГЕТИЧНИХ ХАРАКТЕРИСТИК - Артеменко, М.Ю.; Кутафін, Ю.В.; Чопик, В.В.; Михальський, В.М.; Шаповал, І.А.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2026)
The article proposes a modified structure for the one-port equivalent circuit of linear electric AC networks that reproduces the complex power of the primary circuit and enables time-domain simulation in common computer software. An energy correction factor is introduced, which quantitatively characterises the decrease in the real efficiency of the primary circuit at maximum load power compared to the limit value of 50% for the classical Thevenin circuit equivalent. A one-to-one relationship of this factor with the maximum achievable efficiency of the primary circuit, which can exceed 50% at optimal load, is shown. Using the parameters of the proposed one-port equivalent circuit, analytical relations for calculating the optimal load parameters are obtained. The reliability of the theoretical results is confirmed by computer simulation in the Multisim environment on the example of a linear transformer model, which demonstrated a complete coincidence of the optimised energy characteristics of the primary AC network and its one-port equivalent circuit. References 16, figures 8.